The organization of efficient system of maintenance of locomotives series TGM4 on the example of JSC "Metallurgical plant "Zaporizhstal" - Kapitsa, M. I. (Science and Transport Progress, 2008)
The purpose of work is determination of the rational system of maintenance of the hydromechanical transmission of diesel locomotives of a series ТГМ4 for the beforehand set reliability of locomotive fleet with minimum expenses of funds and labour capacity.